John Brown's raid on Harpers Ferry - Glaser, Jason; Milgrom, A.; Anderson, Bill 1963-; Barnett, Charles (Mankato, Minn. : Capstone Press, 2006)
Tells the story of how John Brown raided the military outpost at Harpers Ferry, Virginia, in 1859, with the goal of capturing weapons and raising an army to fight for the freedom of the slaves.
Includes bibliographical references and index.
9 - 12 years
Keywords: Brown, John -- 1800-1859; Cartoons and comics; Harpers Ferry (W. Va.) -- History -- John Brown's Raid, 1859